2008
DOI: 10.1177/102490790801500102
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Control Trial Comparing the Efficacy of Tramadol and Paracetamol against Ketorolac and Paracetamol in the Management of Musculoskeletal Pain in the Emergency Department

Abstract: Background: This study aimed to compare the efficacy, acceptance and side effects of intramuscular tramadol and ketorolac in combination with oral paracetamol in the emergency setting. Materials and methods: This was a randomised, double blind controlled trial. Patients aged 18 years or above with moderate to severe musculoskeletal pain were recruited. Patients with known allergy, currently on psychiatric medication, with alcohol or opioid dependence, during pregnancy and with major systemic illness were exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Similarly, in patients undergoing hip arthroplasty, preoperative administration of parecoxib offered no advantage compared with postoperative use; opioid-sparing was again seen in both groups compared with placebo (Martinez et al, 2007 Level II). Pain relief was also no better when parecoxib was given before incision compared with administration at the end of surgery in patients undergoing colorectal surgery (Lee et al, 2008 Level II).…”
Section: Chaptermentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, in patients undergoing hip arthroplasty, preoperative administration of parecoxib offered no advantage compared with postoperative use; opioid-sparing was again seen in both groups compared with placebo (Martinez et al, 2007 Level II). Pain relief was also no better when parecoxib was given before incision compared with administration at the end of surgery in patients undergoing colorectal surgery (Lee et al, 2008 Level II).…”
Section: Chaptermentioning
confidence: 97%
“…For acute musculoskeletal pain, IM tramadol was similar to ketorolac in efficacy and side effects, when both were combined with oral paracetamol (Lee et al, 2008 Level II).…”
Section: Tramadolmentioning
confidence: 99%
“…Seven of the 72 included studies [ 56 , 59 , 60 , 62 , 71 , 80 , 87 ] were scored at a high overall risk of bias (eTable 3); all investigated opioid-related adverse events. More than one-third of included studies (25 studies) [ 35 , 36 , 45 , 47 , 51 , 53 , 56 , 57 , 59 , 62 , 63 , 67 , 71 , 73 , 75 , 77 , 80 , 85 , 87 , 88 , 90 , 92 , 94 , 95 , 101 ] were considered as having high or unsure risk of attribution bias due to the lack of reporting of loss to follow-up in randomised controlled trials or data completion rate not reported in observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…17 Lee H et al in his study concluded that tramadol with paracetamol combination is as effective as ketorolac with paracetamol combination. 18 Other studies that concluded ketorolac to be as effective as tramadol were regarding maxillofacial surgery, 19 abdominal surgery. 20 Although we observed both the drugs were having a similar duration of the pain-free interval which proves their effectiveness in pain management, our next concern was safety.…”
Section: Discussionmentioning
confidence: 99%